Could Pan-Islamism Be a Politically Economic Solution in Indonesia? - Syamsuri Syamsuri; Husnul Khotimah; Khoirul Umam (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2022)
The economy in Indonesia is currently not doing well. This can be seen from indonesia's economic growth data which is minus to 5.32 percent, which causes the Indonesian economy to become fragile and requires us to continue to think about how to stabilize the economy again. So a strong analysis and an intelligent way of thinking are needed in overcoming this problem. This study aims to offer a concept from one of the Islamic authorities, namely Jamaluddin Al-Afghani, with his Islamic reform, namely Pan-Islamism in overcoming political economic problems that occur in Indonesia. By using descriptive analytical methods and qualitative approaches that contradicthis thinking, namely Pan-Islamism with several other Islamic scientists' thoughts and coupled with using data from previous studies. Finally, this article presents the concept of political economy which is believed to be able to create a better Indonesian economy. Some of the principles emphasized are the need for the Islamic world to unite together against foreign forces in the crucible of Pan Islamism, because the source of weakness of the Islamic world is the weak solidarity of Muslims. Then Muslims must unite both in political and economic terms, the Leader of the State must spread his call and ideas about reform and renewal in all aspects of life, whether political, economic, social and cultural, are comprehensive for all Muslims around the world where Individuals help each other. So that it can be applied to achieve the political renewal of human economy in this era.